Effectiveness of Macroprudential Policy: Problems of Measurement and Evaluation - G. G. Gospodarchuk; E. S. Zeleneva (Финансы: теория и практика)
The macroprudential policy of central banks plays a key role in ensuring financial stability not only at the level of individual states but also on the scale of the entire global economy. In this regard, adequate measurement of its effectiveness is an urgent task for national and supranational financial regulatory authorities. The present study is focused on solving this problem. The purpose of the study is to develop indicators and criteria for a comprehensive assessment of the effectiveness of countries’ macroprudential policies, allowing for a cross-country analysis of this effectiveness and identifying the best global practices in macroprudential regulation. The study is based on the consolidation of the market and institutional approaches to measuring financial stability, as well as on the use of normative methods and methods of comparative economic analysis. As a result of the study, new indicators for diagnosing the effectiveness of macroprudential policy have been developed. Criteria are proposed to determine the international positions of countries in terms of the level of general, market, and institutional effectiveness of the macroprudential policy. Testing of the developed indicators and criteria was carried out for 180 countries for the period 1998–2019. The developed indicators and criteria for the effectiveness of macroprudential policy differ from the existing ones in a comprehensive manner, since they take into account the stability of financial markets and financial systems at the same time. They are also more representative as they include a wider range of parameters taken into account in financial stability calculations.